INFLUENCE OF GREASE LUBRICATION ON FRETTING-FATIGUE DAMAGES OF STEEL WIRE ROPES - Montalvo, S.; Fouvry, S.; Martinez, M. (Volume 3: Materials Technology; Pipelines, Risers, and Subsea Systems, 2022)
International audience